Recent advances in virulence of a broad host range plant pathogen Sclerotinia sclerotiorum: a mini-review - Zhu, Yangyi; Wu, Chenghong; Deng, Yun; Yuan, Wanlan; Zhang, Tao; Lu, Junxing (Frontiers in Microbiology, 2024)
Sclerotinia sclerotiorum is a typical necrotrophic plant pathogenic fungus, which has a wide host range and can cause a variety of diseases, leading to serious loss of agricultural production around the world. It is difficult to control and completely eliminate the characteristics, chemical control methods is not ideal. Therefore, it is very important to know the pathogenic mechanism of S. sclerotiorum for improving host living environment, relieving agricultural pressure and promoting economic development. In this paper, the life cycle of S. sclerotiorum is introduced to understand the whole process of S. sclerotiorum infection. Through the analysis of the pathogenic mechanism, this paper summarized the reported content, mainly focused on the oxalic acid, cell wall degrading enzyme and effector protein in the process of infection and its mechanism. Besides, recent studies reported virulence-related genes in S. sclerotiorum have been summarized in the paper. According to analysis, those genes were related to the growth and development of the hypha and appressorium, the signaling and regulatory factors of S. sclerotiorum and so on, to further influence the ability to infect the host critically. The application of host-induced gene silencing (HIGS)is considered as a potential effective tool to control various fungi in crops, which provides an important reference for the study of pathogenesis and green control of S. sclerotiorum.